Prevalence and antibiogram of nonfermenting gram negative bacilli isolates obtained from various clinical samples in a tertiary care hospital, Bathinda, Punjab, India - Kaur, Amandeep; Gill, Amarjit Kaur; Singh, Satnam (International Journal of Research in Medical Sciences, 2018)
Background: Non-fermenting gram-negative bacilli (NFGNB) have emerged as important healthcare associated pathogens in recent years. Infections caused by these bacteria are almost always secondary to some predisposing factors in patients such as burns, prolonged antimicrobial therapy, immunosuppression etc. The Objectives of the study was to be carried out with an objective to identify NFGNB upto genus and species level and study their antimicrobial sensitivity/ resistance pattern so that empiric therapy could be selected accordingly. Methods: A total of 2261 clinical samples were collected from patients admitted in ICU and different wards of the hospital. All samples were processed according to standard microbiological procedures. Identification of NFGNB upto genus and species level was done by various biochemical tests. Antimicrobial susceptibility testing was done by Kirby Bauer disc diffusion method results were interpreted in accordance with clinical laboratory standards institute guidelines. Results: In this study, 365 NFGNB were obtained accounting for their prevalence of 16.1%. P. aeruginosa was the commonest NFGNB isolated in this study accounting for 52.6%, A. baumannii was the second common NFGNB isolated (31.7%). Other NFGNB isolates were obtained with a lesser frequency. P. aeruginosa isolates were highly sensitive to polymyxin B and colistin followed by imipenem. Most of the A. baumannii isolates were multidrug resistant. Conclusions: This study gives an alarming sign towards high prevalence of multi drug resistant NFGNB in our hospital. Therefore, improved antibiotic stewardship and strict protocols for hand washing need to be implemented to prevent emergence and spread of multidrug resistant NFGNB in health care settings.